Excavations at King's Low and Queen's Low Two Early Bronze Age Barrows in Tixall, North Staffordshire. - Lock, Gary (Archaeopress, 2014)
Two barrows in the parish of Tixall, north of Stafford, were excavated between 1986-1994. The results are important because little excavation of round barrows has been carried out in this area of North Staffordshire and these add considerably to the local corpus of knowledge concerning Early Bronze Age burial practices.